Saras Cranes in Palwal District in Southern Haryana Are Asking For Immediate Attention for Their Last Rescue Efforts - Kaushik, Tirshem Kumar; Gupta, Rohtash Chand; Vats, Parveen Kumar (Journal of Tropical Life Science, 2015)
Saras Cranes Grus antigone are endangered birds of open wetlands with highly worrying depletion trends being witnessed related with disappearance of marshy and shallow perennial, expansive wetlands throughout northern India. Alongside, massive hunting in 18th, 19th and 20th centuries and even today is another serious cause for their worrisome deterioration. Also, destruction of nests, eggs, fledglings and adults by aboriginals indeliberately or deliberately is causing these cranes to perish sooner than latter, completely.Now, Saras Cranes are found in limited number and domain as four populations in the entire world including India, China, Burma, South East Asia and northern Australia. In so far as Indian Saras Crane population is concerned, it is pitiably restricted to only few hundred in all, in Etawa, Mainpuri districts of Uttar Pradesh, Kanha National Park near Bharatpur in Rajasthan, some parts of Gujarat in the west and Assam in the east.It is interesting to note that few pairs have been seen in Faridabad and Palwal districts in southern Haryana, India. These need to be protected and conserved